Indonesian Interference in Students' Japanese Essays of SMK Penerbangan Cakra Nusantara Schoo (e-Journal of Linguistics, 2020)
This research discusses Indonesian language interference thatoccurs in Japanese essays written by SMK Penerbangan CakraNusantara students. This research aims to describe the types ofinterference found in the form of sentences in students' essays.This research used qualitative descriptive. The subject of thisresearch are students of XII APP 1 class, meanwhile the object ofthis research are interference sentences in Japanese essays. Thedata was collected through note taking technique. The data wasanalysed using a theory proposed by Miles and Hubberman byperforming data reduction, analysing data, and makingconclusions. The results of this research are 1) the types ofinterference that occured based on linguistic aspects aremorphological and syntactic interference; and 2) syntacticinterference occured in three types of interference such aspermutation of core constituents (I) and modifier (M), permutationof predicate (P) and object (O), and ommision of particles (joshi).
Keywords: Interference; Indonesian; Japanese essay